Pendidikan dan Pelatihan terhadap Kinerja Pegawai Kantor Kementerian Agama Kabupaten Karawang - Sophia Anggraeni; Puji Isyanto; Asep Darojatul Romli (IPM2KPE, 2024)
This research aims to evaluate the performance of employees at the Karawang Regency Ministry of Religion Office with a focus on the influence of education and training on their performance. The research approach used is qualitative with descriptive and verification methods. The research results show that there is a significant influence between education and training on employee performance. The research results contribute to the understanding of the factors that influence employee performance in the organizational environment. This research provides valuable information for the management of the Karawang Regency Ministry of Religion Office in designing more effective education and training policies to improve employee performance. In conclusion, the importance of investing in education and training as a strategy to improve employee performance in achieving organizational goals. Keywords: Employee Performance, Ministry of Religion Office, Education and Training, Influence of Education and Training